Personalisasi Komunikasi Media Sosial: Analisis Isi Eiger Adventure dan Psikologi Pengguna - Muhammad Ronaldo Yusran; Hopiatul Islami (MUKASI: Jurnal Ilmu Komunikasi, 2026)
Social media has experienced rapid growth, which has also changed the patterns of corporate communication used to maximize interaction with audiences. One strategy is to personalize corporate communication patterns on social media based on the psychology of social media users. This study aims to analyze how Eiger Adventure utilizes the personalization of corporate communication on their social media. In this study, a descriptive qualitative methodology was employed, applying content analysis to Eiger Adventure's social media content on Instagram, TikTok, X, and Facebook during the period of August 14–21, 2025. The results show that Eiger optimizes Instagram to build a visual image of an adventurous lifestyle, TikTok for interactive entertainment and spontaneous promotion, and X for the rapid distribution of information, opinions, and contextual narratives. Conversely, Facebook is relatively passive, reflecting a shift in focus to platforms that are closer to the younger generation. In conclusion, Eiger's communication strategy is not only product promotion-oriented but also focuses on building emotional connections, community representation, and lifestyle narratives. This study emphasizes that user-psychology-based personalization is a key factor in the success of corporate digital communication in the social media era.